Expression of tenascin in joint-associated tissues during development and postnatal growth. - Mackie, E J (1996)
The extracellular matrix protein, tenascin, is selectively expressed in a variety of connective tissues during development. In this study, the distribution of tenascin in tissues contributing to the knee joint during embryonic development and postnatal growth in the rat has been investigated by immunohistochemistry. In recently formed embryonic knee joints, tenascin expression was abundant in the territorial matrix of superficial articular cartilage. Site of attachment of cruciate and patellar ligaments to cartilage were strongly stained; staining of ligaments weakened with distance from the attachment site. In rapidly growing 4-wk-old rats, tenascin was present in a fine line on the surface of articular cartilage, but at 10 wk of age tenascin staining was absent from most of the articular surface. In postnatal rats, there was strong tenascin staining of the synovial lining, but not of subintimal tissue. Cruciate ligaments were histologically fibrocartilaginous in 4 and 10-wk-old rats; within these ligaments strong pericellular tenascin staining was seen in association with rounded chondrocyte-like cells. Tenascin was absent from the cartilaginous growth plates of 4 and 10-wk-old rats, but intense tenascin staining was seen at the junction between epiphyseal bone and growth plate. Within the metaphysis, tenascin staining on bone surfaces increased with distance from the hypertrophic chondrocytes. Osteocytes within epiphyseal trabecular bone were strongly stained for tenascin, whereas those in the metaphysis were mostly unstained. The results presented here demonstrate that tenascin expression in joint-associated tissues changes markedly with cell type and stage of differentiation.